3D hierarchical nanostructured Ni–Co alloy electrodes on porous nickel for hydrogen evolution reaction. (15th November 2019) - Zhang, Xundi; Li, Ya; Guo, Yukun; Hu, Anmin; Li, Ming; Hang, Tao; Ling, Huiqin
Abstract: Nanostructured Ni–Co alloys decorated on 3D porous nickel electrodes for hydrogen evolution reaction (HER) are successfully prepared through a facile and effective electrodeposition method. By adjusting the current density of electrodeposition, Ni–Co alloys with different surface morphologies like nanocones, leaf-like structures and flakes can be obtained. The HER catalytic activity has been greatly reinforced with decorated Ni–Co alloys. Meanwhile, the HER performance of nanocone Ni–Co alloys outperforms that of leaf-like and flaky Ni–Co alloys. The nanocone Ni–Co alloys exhibit outstanding HER activity, only requiring an overpotential of 86.7 mV at 10 mA cm −2, along with a low Tafel slope of 69.8 mV dec −1 and 3.4 Ω charge transfer resistance. This nanocone electrode remains stable for 10 h of chronopotentiometric measurement. Such enhanced catalytic performance stems from the porosity and the high population of sharp edges, as well as surface oxidation/metallic states and synergistic effects between Ni and Co. Graphical abstract: Image 1 Highlights: Different Ni–Co structures were synthesized by adjusting electrodeposition condition. The nanocone Ni–Co alloys on porous Ni manifest highest electrocatalysis activity. 10 h of durability measurement shows high stability of the 3D nanostructure.